2019
DOI: 10.7249/rr3033
|View full text |Cite
|
Sign up to set email alerts
|

Prices Paid to Hospitals by Private Health Plans Are High Relative to Medicare and Vary Widely: Findings from an Employer-Led Transparency Initiative

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 36 publications
3
79
2
Order By: Relevance
“…Also, we cannot determine how hospitals are allocating costs but that is not the purpose of this study. Finally, we made adjustments for payment source but these were based on published literature estimating the differences in Medicare and private insurance payments [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, we cannot determine how hospitals are allocating costs but that is not the purpose of this study. Finally, we made adjustments for payment source but these were based on published literature estimating the differences in Medicare and private insurance payments [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that private insurance pays more and Medicaid pays less than Medicare [22][23][24][25][26][27][28]. We utilized data from these reports to adjust payment rates by insurer type to account for differences in payment rates by payer [22][23][24][25][26][27][28]. Based on these published reports, we created a conservative and upper estimate of payment for inpatient cases:…”
Section: Reimbursement Variablementioning
confidence: 99%
See 1 more Smart Citation
“…19 Concurrently, these same practices also benefit from provider leverage in establishing higher payment rates for privately insured patients in the hospital outpatient setting. 20 the years. 21 Another study found that hospitals eligible for the 340B program had more hematologist-oncologists (230 percent more) compared to non-340B participating hospitals.…”
Section: Impac T Of 4 0 B On C Are Pat Tern Smentioning
confidence: 99%
“…The cost of test and physician visits were estimated using the physician fee schedule from Centers for Medicare and Medicaid Services (CMS) for study population of ages 66 and above and a conversion factor (229%) was used to estimate the screening cost for privately insured population below 66 years of age. This conversion factor used to estimate the screening cost under private health plans was taken from a study conducted by Rand Corporation 14…”
Section: Illustration Of the Value Of Diabetes Preventionmentioning
confidence: 99%